Analysis of Factors That Influence Hypertension in Community Ages 20-40 Years in The Work Area of The Habinsaran Public Health Center, Toba Regency - Megawati Sinambela (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Hypertension is often referred to as "The Silent Killer" or the silent killer which is now more common in young people. For the occurrence of hypertension, it is necessary to play the role of these risk factors together (common underlying risk factors), in other words, one risk factor alone is not sufficient to cause hypertension. The purpose of this study was to analyze the factors that influence the occurrence of hypertension in people aged 20-40 years in the work area of the Habinsaran Public Health Center, Toba Regency in 2020. This type of research is an observational study with a case control study design with a total of 46 people in the case group and 46 people in the control group. The analysis used in this research is univariate, then the bivariate test using the Chi Square test and the multivariate test using multiple logistic regression tests. The results showed that the educational factor with an OR value of 3.276 (95% CI: 1.310– 8.194) and smoking habits with an OR value of 2.788 (95% CI: 1.145– 6.788) were significant factors affecting the incidence of hypertension in people aged 20-40. Year. The factor that most influences the incidence of hypertension in people aged 20-40 years in the work area of Puskesmas Habinsaran, Toba Regency in 2020 is the factor of education. It is advisable to activate Posbindu PTM and Prolanis in the community by conducting early detection and capturing people who have a family history of hypertension so that cases can be known and handled early, especially in young people. As well as improving existing preventive programs so that they can recruit more hypertension sufferers at Habinsaran Community Health Center.